Dietary, Lifestyle and Children Health - Zou, Zhiyong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Food quality, including dietary quality and diversity, is as essential to human health as air is to human life. In addition, other healthy lifestyle factors, including a healthy body mass index, regular exercise, no smoking, and sufficient sleep duration, are associated with a lower incidence of chronic non-communicable diseases and longer life expectancy. More importantly, maternal healthy lifestyle factors are also associated with a substantially reduced risk of chronic diseases in their offspring. Childhood is a critical period for the development of a healthy lifestyle and the prevention of chronic diseases in adulthood. However, the prevalence of childhood obesity is increasing and unhealthy lifestyles are becoming an epidemic, posing a potential future burden of adult chronic disease. The aim of this Special Issue is to identify and assess dietary factors, including dietary diversity and specific nutrients/phytochemicals, as well as other healthy lifestyle factors, in the prevention and management of childhood chronic diseases. Additionally, we want to identify gaps and tools that could help with the assessment of children's health. We wanted to encourage all researchers who work in this field to submit original research, reviews, systematic reviews, and meta-analyses to this Special Issue to broaden our knowledge and pave the way for new research directions.